Voter turnout at the national level in Poland – selected aspects - Rachwał, Marcin (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa, UAM, 2020)
The article addresses the issue of voter turnout at the national level in Poland in 1990–2019. In particular, the author focused on 2019, when the turnout in parliamentary elections was the highest throughout the period under analysis. The aim of the study is to determine the reasons for this increase in the electoral activity of Polish citizens. The analysis leads to the conclusion that after the Law and Justice party took power in 2015, significant modifications of the social system, including the political system, ensued, thereby altering selected features of the electoral situation and raising the level of political emotions. The outcome involved a significant increase in voter turnout in 2019, when the elections to the European Parliament, as well as to the Polish parliament (the Sejm and Senate) were held. The study employs the following methods: analysis and criticism of literature (sources), the systemic method, and statistical methods.

Przedmiotem artykułu jest zagadnienie frekwencji wyborczej w Polsce na poziomie ogólnokrajowym w latach 1990–2019. W szczególności autor skupił uwagę na roku 2019, gdyż zanotowano wówczas najwyższą frekwencję w wyborach parlamentarnych w analizowanym okresie. Celem badań było ustalenie przesłanek, które miały wpływ na wskazaną sytuację, na wzrost aktywności wyborczej obywateli RP. Przeprowadzona analiza skłania do wniosku, iż po przejęciu władzy przez Prawo i Sprawiedliwość w 2015 roku doszło do istotnych modyfikacji systemu społecznego, w tym politycznego, co przyczyniło się do zmiany wybranych cech sytuacji wyborczej i podwyższenia poziomu emocji politycznych. Konsekwencją był znaczny wzrost frekwencji wyborczej w 2019 roku, gdy odbyły się wybory do Parlamentu Europejskiego, jak również do Sejmu i Senatu. Podczas badań zastosowanie znalazły: metoda analizy i krytyki piśmiennictwa (źródeł), metoda systemowa, metody statystyczne.
Frekwencja wyborcza w Polsce na poziomie ogólnokrajowym – wybrane aspekty zagadnienia
Keywords: democracy; illiberal democracy; political participation; elections; voter turnout; demokracja; demokracja nieliberalna; partycypacja polityczna; wybory; frekwencja wyborcza